Low Mach number limit for the full compressible Navier–Stokes equations with Cattaneo's heat transfer law. (July 2019) - Zhang, Shuxing
Abstract: In this paper, we study the low Mach number limit for the full compressible Navier–Stokes equations with Cattaneo's heat transfer law. It is rigorously justified that, in the framework of classical solutions with small density, temperature and heat flux variations, the solutions of the full compressible Navier–Stokes equations with Cattaneo's heat transfer law converge to that of the incompressible Navier–Stokes equations as the Mach number tends to zero.